A new digital resonant current controller for AC power converters based on the advanced Z-transform. (October 2022) - Stojić, Đorđe M.; Šekara, Tomislav B.
Abstract: In this paper, we present a new digital resonant current controller that can be applied in single-phase and three-phase alternating current (AC) power converters, based on voltage source inverters (VSI) with pulse width modulation (PWM). Since power converters based on PWM introduce fractional time delays regarding the sampling period ( T s ), because of the current sampling and PWM command updating techniques that are employed, there is a need to develop analytical tools for precise modelling of these types of delays. To achieve this, the advanced Z-transform is applied in order to model the AC controllers in VSIs with PWM for the general case of a fractional time delay, including power converters with current sampling within a PWM period at any chosen time instance. This new approach to power converter modelling and current sampling allowed us to develop a modified resonant AC current controller for a VSI with RL load, based on the pole-placement parameter tuning method. It includes fractional time delays, which are conventionally employed in the power converter design, in the controller parameter derivations, and introduces the minimal order resonant controller that enables strict placement of all closed-loop control system poles. Simulations and experimental tests are carried out to show the improvements introduced by novel solution in this paper compared with conventional resonant current controllers. In the analysis of dynamic performance and robustness, in this paper conventional indices are applied to compare the proposed controller with a conventional design. Highlights: The introduction of the Advanced Z-Transform enables analytical modelling of the plant that includes a fractional time delay. Novel pole-placement based parameter tuning procedure is presented, which places all closed-loop system poles at required positions. New controller is compared with existing solution by test runs and conventional dynamic performance and robustness indices.